Soil Carbon Accumulation and Nutrient Availability in Managed and Unmanaged Ecosystems of East Tennessee. Issue 2 (29th April 2019) - Singh, Shikha; Yan, Sheng; Sorochan, John; Stier, John; Mayes, Melanie A.; Zhuang, Jie; Jagadamma, Sindhu
Abstract : Core Ideas: Native woodlot and grassland systems have been converted to a managed turfgrass system with urbanization. Turfgrass systems increased carbon sequestration and nitrogen availability compared with row crop systems. Cool‐season (C3 ) turfgrasses improved soil physical and chemical properties more than warm‐season (C4 ) grasses. In the last two decades, urban and suburban lands grew by 34% in the United States, with 16 to 20 million ha maintained under turfgrass systems. Side‐by‐side comparison of turfgrass systems with other managed and unmanaged ecosystems have not been comprehensively conducted in the climate transition zone of the United States, despite the environmental significance of land use changes. Our objective was to determine the relative effects of C3 and C4 turfgrasses on soil organic carbon (SOC) accumulation and nutrient availability, in comparison with managed row crop and unmanaged woodlot and grassland systems. Soil samples from depths of 0 to 5, 5 to 15, and 15 to 30 cm were collected during March 2017 at the University of Tennessee's East Tennessee Research and Education Center from seven ecosystems: (i) corn ( Zea mays L.)–soybean ( Glycine max L.) rotation, (ii) continuous soybean, (iii) tall fescue ( Festuca arundinacea L.), (iv) Kentucky bluegrass ( Poa pratensis L.), (v) bermudagrass ( Cynodon dactylon L.), (vi) unmanaged grassland, and (vii) unmanaged woodlot. All turfgrass species were established in 2012 and were managed like low‐input residential lawns. Within the 30‐cm soil profile, turfgrass systems contained 4.2 kg m −2 SOC at the time of sampling, which was 33% more than croplands and 34% less than unmanaged systems, and the C4 turfgrass system contained 2.3 kg m −2 SOC and 0.4 mg kg −1 inorganic N, which were 56 and 57% lower than C3 systems, respectively. Results from this study highlight that low‐input lawns with suitable grass species can offer higher SOC stock and nutrient availability than conventional cropland systems.